Zn–Air Batteries: All‐Hand‐Drawn Zn–Air Batteries: Toward User‐Customized On‐the‐Fly Power Sources (Adv. Sustainable Syst. 5/2018). (9th May 2018) - Choi, Keun‐Ho; Kim, Hyun‐Woo; Lee, Seong‐Sun; Yoo, JongTae; Lee, Dong‐Gue; Lee, Sang‐Young
Abstract : In article number1700132, Sang‐Young Lee and co‐workers demonstrate all‐hand‐drawn primary zinc (Zn)‐air batteries as a new class of user‐customized, on‐the‐fly power sources. The all‐hand‐drawn Zn‐air batteries are fabricated directly on A4 paper under ambient conditions by using a simple pen/pencil‐based hand drawing technique, exhibiting their unique "on‐demand"/"on‐site" fabrication. The all‐hand‐drawn Zn‐air batteries are aesthetically unitized with arbitrary‐shaped IoT devices.